LncRNA ILF3AS1, MMP3, and MMP9 as well as miRNA-212 as emerging novel biomarkers for childhood epilepsy - Mohammed, Amena Rezk; Emam, Wafaa Abdelaziz; Mohammed, Shaymaa A.; Abd Elalim, Alshaymaa A.; Mansour, Eatemad Nabil Abdelhalim; Nasr, Haidy Mahmoud; Ghamry, Aya A.; Alkhawagah, Sabah M.; Fathy, Doaa Sadek Ahmed; Elattar, Rasha Sobhy; Abish, Yasser Gaber Ibrahim; Hussein, Abdullah; et al. (Frontiers in Molecular Biosciences, 2024)
Background: Approximately 70 million people suffer from epilepsy worldwide. Infants representing significant percentage of cases. Therefore, there is a significant need for a greater understanding of the pathophysiology of epilepsy using laboratory and radiological methods for early detection and optimized management. Interleukin enhancer-binding factor 3-antisense RNA l (ILF3-AS1) is a LnRNA that enhances the expression of matrix metalloproteinase 3 (MMP3) and matrix metalloproteinase 9 (MMP9), which are all thought to be epileptogenic.We aimed to assess serum expression of LncRNA ILF3AS1, MMP3, MMP9, and microRNA 212 (miRNA-212) as predictive biomarkers in children with epilepsy and assessing their correlations with magnetic resonance imaging (MRI) findings.Fivty children with epilepsy and 50 healthy controls. Serum expression of LncRNA ILF3ASI and miRNA-212 were estimated by s q-PCR. Serum concentrations of MMP3 and MMP9 were estimated by ELISA in parallel with the magnetic resonance imaging (MRI) findings and different baseline biochemical parameters of all included subjects.The study revealed significantly higher levels of Lnc RNA ILF3AS1, MMP3, and MMP9 and lower levels of miR-212 in children with epilepsy compered to controls. Fold-change miR-212 was a significant negative predictor (OR= 0.153, P=0.000). The receiver operating characteristic (ROC) curve showed that the areas under the curves (AUC) for MMP3, MMP9, lncRNA ILF3AS1, and fold-change miRNA212 were 0.659, 0.738, 0.656 and 0.965, respectively. Brain lesions were detected in 15 patients (30%) with epilepsy, whereas the remaining 35 patients (70%) had normal results.LncRNA ILF3AS1 serum levels among children with epilepsy children were higher than those in the control group and were associated with the upregulation of MMP3 and MMP9 and the downregulation of miR-212 expression, suggesting their predictive utility in monitoring the development of epilepsy and that a treatment plan that focuses on the ILF3-AS1/miR-212/MMP3 & 9 axis may be an effective strategy for treating epilepsy.